Analysis of Building Structure Dynamics Due to Earthquake Loads - Mely Anisa; Lindung Zalbuin Mase; Hardiansyah Hardiansyah; Rena Misliniyati; Khairul Amri (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
This study aims to assess the impact of earthquakes on the Professional Programme Lecture Building at the Faculty of Teacher Training and Education (FTTE), Bengkulu University, by integrating soil response analysis and structural dynamics. The research began with the collection of geological data at the research site. Seismic soil response analysis was conducted to assess soil movement at the end of the piles, followed by earthquake wave propagation to evaluate the building's response to earthquake activity using the Finite Element Method (FEM). Based on load ratio evaluations, beam B2 and column C2 on the second floor of the building were identified as having structural weaknesses. Therefore, retrofitting techniques were applied to increase the load capacity of the structure. The results showed that retrofitting provided significant improvements in structural performance. This research highlights the importance of integrating soil response analysis with structural dynamics to enhance the resilience and safety of buildings in earthquake-prone areas.